307 The prevalence and burden of health problems in competitive adolescent distance runners: a prospective study in England. (3rd March 2020) - Mann, Robert; Barker, Alan; Williams, Craig; Clift, Bryan
Abstract : Background: Little is known about the overall health of adolescent distance runners. Objective: What is the prevalence and burden of health problems (i.e. injuries and illnesses) in competitive adolescent distance runners? Design: A prospective cohort study monitoring all health problems for 24-weeks, between May and October (2019). Setting: Competitive adolescent distance runners (i.e. 800 m to 10, 000 m, including steeplechase) in England. Patients (Or Participants): Distance runners (13–18 y) were invited (via letter sent to their athletics club) to participate if they had achieved a top-50 performance in their age-group (U20, U17 and U15) during 2018. A total of 644 athletes were invited to take part, with 137 athletes (74 females) having enrolled and completed the study (lost to follow-up: n=7). Main outcome measurements: The prevalence and burden of health problems was recorded using the Oslo Sports Trauma Research Center Questionnaire on Health Problems (OSTRC-H). The OSTRC-H was completed online, via Qualtrics, on a weekly basis. 'Burden' is reflective of both severity and incidence. Results: A total of 389 health problems were registered during this study, including 219 injuries and 170 illnesses. An average of 26% [95% confidence intervals: 23–29%] reported symptoms from injury or illness, and 11% [10–12%] experienced health problems with a substantial negative impact on training and performance. Illnesses represented the greatest incidence (3.0 cases per athlete per year), while overuse injuries represented the greatest prevalence (12% [10–14%]). The total burden of health problems was also highest in overuse injuries (47%), when compared to illnesses (31%) and acute injuries (22%). The most burdensome overuse injuries were to the lower leg, knee and foot/toes. Conclusions: The greatest prevalence and burden of health problems to competitive adolescent distance runners is from overuse injury followed by illness and acute injury. Future prevention efforts should focus on overuse injuries located in the lower leg, knee and foot/toes.